PERANAN MODAL SOSIAL DALAM KEMITRAAN KEHUTANAN DI TAMAN NASIONAL BUKIT BARISAN SELATAN - Kurniasari, Nanda; Wulandari, Christine; Bakri, Samsul; Dewi, Bainah Sari; Safe’i, Rahmat; Sugiharti, Tri (Jurnal Hutan Tropis, 2024)
Problems with the community regarding the use of Non-Timber Forest Products (NTFPs) in national park areas are one of the debates that are often faced, including in the Bukit Barisan Selatan National Park. The effectiveness of implementing forestry partnerships based on the perspective of the community as permit holders is something that must be done to resolve this problem. A person's perspective based on their perceptions is usually influenced by demographics and social capital, so it is necessary to know whether both have an influence on forestry partnership programs. Many studies have proven that, in particular, the success of forest management with the community cannot be separated from the contribution of social capital, especially through the variables of trust, social norms and existing social networks. So far, there has been a lot of research on forestry partnerships in national parks that has been linked to the success of increasing production, but still very little has been linked to the characteristics and social aspects of the community. Based on this, the aim of this research is to analyze the role of social capital in the implementation of forestry partnerships in the Bukit Barisan Selatan National Park. The research was conducted in July 2023 with a sample of 95 respondents who were members of the partnership program. Data analysis through hypothesis testing Partial Least Square- Structural Equation Model (Second Order) using Smart PLS.4.0 software. The results of hypothesis testing show that social capital variables (trust, norms/values, and networks) influence partnership members to participate in the program. The level of social capital owned by the community shows the level of trust from both internal and external groups, the level of compliance with the rules and the level of motivation to build a stronger marketing network by involving the roles of the parties.